2021
DOI: 10.3390/cosmetics8020053
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Aging Potential of Indian Sandalwood Oil against Environmental Stressors In Vitro and Ex Vivo

Abstract: Distilled from the heartwood of Santalum album, Indian sandalwood oil is an essential oil that historically has been used as a natural active ingredient in cosmetics to condition and brighten the skin. It has been documented to exhibit antioxidant, anti-inflammatory, and anti-proliferative activities. Here, we investigated the protective and anti-aging effects of Indian sandalwood oil in scavenging reactive oxygen species (ROS) in HaCaT cells and in human skin explants after exposure to oxidative stress. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…An ideal regimen of daytime protection would include reduced exposure to blue light and prevention or minimization of free radical formation (Table 4) [22,34,[46][47][48][49][50][51]. An ideal regimen of night-time repair would include greater protection of the opsin photoreceptors against activation, collagen against degradation, mitochondria against damage, and DNA against oxidation, as well as other methods (Table 4) [11,29,[51][52][53][54][55][56][57][58][59][60][61].…”
Section: Indirect Effects Of Blue Lightmentioning
confidence: 99%
“…An ideal regimen of daytime protection would include reduced exposure to blue light and prevention or minimization of free radical formation (Table 4) [22,34,[46][47][48][49][50][51]. An ideal regimen of night-time repair would include greater protection of the opsin photoreceptors against activation, collagen against degradation, mitochondria against damage, and DNA against oxidation, as well as other methods (Table 4) [11,29,[51][52][53][54][55][56][57][58][59][60][61].…”
Section: Indirect Effects Of Blue Lightmentioning
confidence: 99%
“…The authors identified three new compounds: copriqunolinone, spirobenzofuranone, and hydrate of deoxyspirobenzofuran. The antioxidant property of Indian sandalwood oil is stronger than that of vitamin E, as demonstrated by in vitro research on the human keratinocyte cell line and ex vivo studies on human skin explants [ 226 ]. A recent clinical study revealed that skin treated with Indian sandalwood oil was protected against blue light exposure [ 223 ].…”
Section: Antioxidant Treatmentsmentioning
confidence: 99%
“…In general, natural products can be potentially antiaging active ingredients in cosmetics, such as S. macrophylla seed extract as an anti-UVB photoprotective ingredient [6] and sandalwood oil as an environmental stress-protective ingredient [28].…”
Section: Antiaging With In Vivo Animal Skinmentioning
confidence: 99%
“…The lowest score was observed in subjects with nutmeg and clove oil treatments, as well as UVB exposure. Therefore, essential oils have the potential to repair damaged aging skin caused by UVB exposure [28]. In general, natural products can be potentially antiaging active ingredients in cosmetics, such as S. macrophylla seed extract as an anti-UVB photoprotective ingredient [29] and sandalwood oil as an environmental stress-protective ingredient [30].…”
Section: Antiaging With In Vivo Animal Skinmentioning
confidence: 99%
See 1 more Smart Citation